When Death Knocks - Reza Fiyouzat (Revista Espaço Acadêmico, 2021)
When death knocks at our door, announcing the last breaths allowed, and after we have taken in the last views of the world as we’ll ever know it, what then? Well, from one perspective, there are of course the rites and the rituals, which in all cultures are to be respected, intricate, and involved. Intricate and involved precisely because death has always been, is and will be with us. From the moment we have life, death is a given. As the Farsi saying goes, ‘It’s a camel that sleeps behind all our doors.’ In Iran, a predominantly Shiite Muslim country, these rites and rituals are as intricate as can be. Their extent covers the mannerisms of family members at the death bed all the way to the duties of the mourners up until a year after the death.